Women and the breadwinning roles: the place of entrepreneur education (2022)
Men's major function in most African communities, Nigeria being no exception, is being the breadwinners for the family. Nonetheless, as more women obtain education and join paid employment, and as some men lose jobs, conventional breadwinning roles are challenged and, in some cases, inverted, thereby making an increasing percentage of women family breadwinners. Women breadwinners may have an impact on family stability since they challenge established normative gender order in Nigerian patriarchal society. Now that more women are entering breadwinning positions unprepared for, with the majority lacking formal education and training, there is a need for each woman to develop a conscious and purposeful strategy to ensure that she is able to fit in correctly in the breadwinning role status. As a result, there is a need for entrepreneurial education for women. Furthermore, entrepreneurship is a deliberate endeavor aimed at beginning, developing, inventing, and mainstreaming economic activity for the generation and distribution of wealth. As a result, women's entrepreneurship development might be viewed as a feasible path to economic emancipation. A woman entrepreneur is more economically powerful than a worker since ownership, not only imparts control over assets but also allows her to make decisions. As a result, this article investigates women and their breadwinning duties, as well as encouraging women to sustain the Nigerian economy through entrepreneurial education. As a result, this article investigates women and their breadwinning duties, as well as encouraging women to sustain the Nigerian economy through entrepreneurial education.